ANALISIS TINGKAT KEPUASAN PENGGUNA TERHADAP PENERAPAN LEARNING MANAGEMENT SYSTEM (LMS) UJIAN ONLINE MENGGUNAKAN METODE E-SERVQUAL - Winarso, Doni; Rudy Asrianto; Irfan Al Rasyid (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2022)
Muhammadiyah Bangkinang High School. SMA Muhammadiyah Bangkinag is one of the schools under the Muhammadiyah organization. The Learning Management System (LMS) owned by this school is Muhammadiyah Online Learning (MOLA). The method used in this research is the Electronic Service Quality (E-Servqual) method. This e-Servqual method has seven dimensions, namely efficiency, reliability, responsiveness, privacy,fulfillment, compensation and contact. The purpose of this study was to determine how much influence the quality of the online MOLA exam LMS on user satisfaction. The sampling technique in this research is using random sampling technique. From the resultsof the F test as a whole, the calculated F value is 34,159 > F table 2,10, so it can be concluded that H1 is accepted which means that there is an effect of the E-Servqual variable (X) having a simultaneous (simultaneous) effect on the user satisfaction variable (Y). ). For the results of R square has a value of 0.727, this means that the effect of the E-Servqual variable together or simultaneously in explaining the dependent variable, namely the user satisfaction variable (Y) is 72%. Based on the results of data processing, it shows that the level of user satisfaction with the implementation of the Learning Management System (LMS) online exam according to students is not satisfactory because there are variables that have negative values.